2017
DOI: 10.1590/1983-21252017v30n206rc
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as Soil Conditioner in the Succession of Upland Rice and Cowpea Fertilized With Nitrogen

Abstract: -The effects of biochar and nitrogen application on yields of upland rice and cowpea and on soil fertility were determined in a greenhouse in Macaíba, RN, Brazil. The trial consisted of the succession of two crops in a completely randomized design and a factorial scheme, with four replicates. Initially, four doses of biochar and four doses of nitrogen were tested for cultivation of rice. Subsequently, four doses of biochar and two doses of nitrogen were tested in half of the pots maintained for planting cowpea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…In our study, biochar application inconsistently affected weight of 1000 grains (Table 4). Similar results were reported by Miranda et al (2017). Increasing yield due to biochar application also was reported by Asai et al (2009).…”
Section: Effects On Yield Componentssupporting
confidence: 88%
“…In our study, biochar application inconsistently affected weight of 1000 grains (Table 4). Similar results were reported by Miranda et al (2017). Increasing yield due to biochar application also was reported by Asai et al (2009).…”
Section: Effects On Yield Componentssupporting
confidence: 88%
“…For instance, eucalyptus green waste biochar produced at 650-750 °C had 7000 mg kg −1 Fe (Abujabhah et al 2016); whereas, willow wood waste biochar produced at 550 °C had only 0.05 mg kg −1 Fe (Agegnehu et al 2016a). Several other studies (Brantley et al 2016;Chen et al 2018;Li and Shangguan 2018;Miranda et al 2017;Noyce et al 2017) also reported that biochar contains a low but significant amount of micronutrients.…”
Section: Trace Elementsmentioning
confidence: 92%
“…Thomas, 2019), pois afeita o pH (Miranda et al, 2017), aumenta o teor de N e P (Gale et al, 2017) e a liberação de íons é gradual (principalmente Ca 2+ , Mg 2+ , K + ) (Gale e Thomas, 2019).…”
Section: O Ble Representa Propriedades Que Promovem O Crescimento Das...unclassified